Annual Cover Crops in Florida Vegetable Systems Part 2: Production - Danielle Treadwell; Waldemar Klassen; Michael Alligood (EDIS)
HS-1141, a 10-page illustrated fact sheet by Danielle Treadwell, Waldemar Klassen, and Michael Alligood, is the second part of the three-part series, Annual Cover Crops in Florida Vegetable Systems. It discusses management practices for annual cover crops, from seed selection to termination. Includes references. Published by the UF Department of Horticultural Sciences, July 2008.